Biodegradable AIEgen-functionalised mesoporous bioactive glass nanoparticles for drug delivery and cell imaging. Issue 2 (9th January 2018) - Wang, Duo; Zhang, Chengkai; Ren, Li; Li, Dongdong; Yu, Jihong
Abstract : AIEgen-functionalised mesoporous bioactive glass nanospheres with excellent degradability in an acid environment show potential application in drug delivery and cell imaging. Abstract : Inorganic bioactive nanomaterials play a significant role in biomedical fields due to their excellent biocompatibility. AIEgen-functionalised mesoporous bioactive glass (FMBG) nanoparticles with sizes of 60–100 nm are prepared by post-grafting tetraphenylethene onto bioactive glass. The obtained nanoparticles emit strong blue light at 482 nm upon UV irradiation, showing potential application in cell imaging. Furthermore, the FMBG, with a high DOX loading capacity of 250.74 μg mg −1 and good degradability in an acid environment, can be used for cancer treatment. The degradability of FMBG increases the release efficiency of DOX in the acid environment. The as-prepared hybrid nanoparticles may act as a promising drug delivery system due to their high drug loading capacity, pH sensitivity, good biodegradability, and biocompatibility.